A Hybrid Supramolecular Polymeric Nanomedicine for Cascade‐Amplified Synergetic Cancer Therapy. (5th May 2022) - Yang, Kai; Qi, Shaolong; Yu, Xinyang; Bai, Bing; Zhang, Xueyan; Mao, Zhengwei; Huang, Feihe; Yu, Guocan
Abstract: Supramolecular nanomedicines have shown great merits in cancer therapy, but their clinical translation is hampered by monotonous therapeutic modality and unsatisfactory antitumor performance. Herein, a hybrid supramolecular polymeric nanomedicine (SNPs ) is developed based on β‐cyclodextrin/camptothecin (CPT) host−guest molecular recognition and iron‐carboxylate coordination. Iron ions stabilizing SNPs catalyze the conversion of intracellular hydrogen peroxide into highly toxic hydroxyl radical through a Fenton reaction, which further cleaves the thioketal linker of the supramolecular monomer to release potent CPT, thus amplifying the therapeutic efficacy by combining chemodynamic therapy and chemotherapy. The combination therapy stimulates antitumor immunity and promotes intratumoral infiltration of cytotoxic T lymphocytes by triggering immunogenic cell death. In synergy with PD‐L1 checkpoint blockade, SNPs enables enhanced immune therapy and a long‐term tumor remission. Abstract : A hybrid supramolecular polymeric nanomedicine for cascade‐amplified synergetic chemodynamic therapy and chemotherapy is constructed based on β‐cyclodextrin/camptothecin host−guest molecular recognition and iron‐carboxylate coordination. In synergy with a checkpoint blockade, this supramolecular nanomedicine leads to an enhanced therapeutic performance and long‐term tumor remission.